IKLIM KOMUNIKASI ORGANISASI PADA DINAS TENAGA KERJA DAN TRASMIGRASI UNIT PELAKSANA TEKNIS BALAI LATIHAN KERJA SURABAYA - Dea Nofita Setyaningrum; Leonard Adrie Manafe; Safaat Safaat (ITB AAS Indonesia Surakarta, 2023)
The organizational communication climate is an important factor because in communication there is social interaction characterized by an exchange of meanings to unite the behavior or actions of each individual. With communication, it will be easier to convey information to achieve the main goals of the company or agency. This study aims to determine the organizational communication climate at the Dinas Tenaga Kerja Dan Trasmigrasi Unit Pelaksana Teknis Balai Latihan Kerja Surabaya. This study uses descriptive methods with qualitative data, to describe the overall research results of an event. Observation using interview techniques in this study was chosen as a data collection process, where the object was an employee of UPT BLK Surabaya. The results showed that the organizational communication climate with the dimensions of Supportiveness, namely description, problem orientation, spontaneity, empathy and similarity are all well intertwined. Such as support provided by leaders to employees and fellow employees, decision making that is always deliberated and involves employees, as well as providing rewards that aim to increase productivity and encourage better performance.